For the love of our children: an Indigenous connectedness framework. (June 2019) - Ullrich, Jessica Saniguq
This article draws on Indigenous literature to develop a conceptual framework that makes visible Indigenous child wellbeing. A process of qualitative content analysis identified and examined the core concepts and mechanisms of Indigenous wellbeing. Central to the framework is the concept of connectedness. The premise of this article is that deepening our understanding of Indigenous connectedness can assist with the restoration of knowledge and practices that promote child wellbeing. When children are able to engage in environmental, community, family, intergenerational and spiritual connectedness, this contributes to a synergistic outcome of collective wellbeing. The Indigenous Connectedness Framework may be particularly useful to Indigenous communities that directly serve children. The hope is that communities can adapt the Indigenous Connectedness Framework to their particular history, culture, stories, customs and ways of life.